Lessons Learned, Resilience Built, and Multipolarism Imagined: The Muslim Experience of the 2019-2022 Pandemic Crisis - Halim, Fachrizal A. (Sekolah Tinggi Agama Islam Syekh Abdur Rauf Aceh Singkil, Aceh, Indonesia, 2024)
This article examines Muslims' responses to the COVID-19 pandemic from 2019 to 2022, including their efforts to overcome the crisis and envision a post-pandemic global society. This study aims to outline three main categories of Muslim efforts: (1) rejection of biopolitical action, (2) resistance to ongoing crises, and (3) promotion of the common good and imagination of a multipolar world. The method used in this study is qualitative analysis through literature review and case studies describing various responses of Muslim communities to the pandemic. The results show that despite the challenges, the pandemic has provided a unique opportunity for Muslim individuals and communities to reflect and rethink a more just and equal world. Many Muslims recognize the need for greater international cooperation and equitable distribution of resources, leading to a movement towards multipolarity. The author argues that the concepts, ideas, and strategies offered by Muslims can be an alternative to the dominant Western concepts and categories. This allows individuals to interact, enrich each other's points of view, and commit to achieving the common good without getting caught up in ideological or nationalistic excitement. [Abstrak Artikel ini mengkaji respons Muslim terhadap pandemi COVID-19 dari tahun 2019 hingga 2022, termasuk upaya mereka dalam mengatasi krisis dan membayangkan masyarakat global pasca-pandemi. Penelitian ini bertujuan untuk menguraikan tiga kategori utama upaya Muslim: (1) penolakan terhadap tindakan biopolitik, (2) perlawanan terhadap krisis yang berkelanjutan, dan (3) promosi kebaikan bersama serta imajinasi dunia multipolar. Metode yang digunakan dalam penelitian ini adalah analisis kualitatif melalui tinjauan literatur dan studi kasus yang menggambarkan berbagai respons komunitas Muslim terhadap pandemi. Hasil penelitian menunjukkan bahwa meskipun menghadapi berbagai tantangan, pandemi telah memberikan kesempatan unik bagi individu dan komunitas Muslim untuk merefleksikan dan memikirkan kembali dunia yang lebih adil dan setara. Banyak Muslim mengakui perlunya kerja sama internasional yang lebih besar dan distribusi sumber daya yang adil, yang mengarah pada gerakan menuju multipolaritas. Penulis berpendapat bahwa konsep, gagasan, dan strategi yang ditawarkan oleh Muslim dapat menjadi alternatif terhadap konsep dan kategori dominan Barat. Hal ini memungkinkan individu untuk berinteraksi, memperkaya sudut pandang satu sama lain, dan berkomitmen untuk mencapai kebaikan bersama tanpa terjebak dalam kegembiraan ideologis atau nasionalistik.]